Microsoft Office Training for the Microcredential Program and BNSP Certification through a Professional Certification Institute at Universitas IBBI - W. Wilianto; L. Lusiah; Edison Parulian; Lenny Menara Sari Saragih; Satriya Miharja; Lili Suryati (Golden Ratio of Community Services and Dedication, 2026)
The Microsoft Office training program, covering Microsoft Word, Microsoft Excel, and Microsoft PowerPoint, was organized by IBBI University as part of its Microcredential Program in preparation for certification by the National Professional Certification Agency (BNSP) under the Data Management Staff scheme. The training was held on April 10, 2026, in Computer Laboratory 215 at IBBI University, followed by the microcredential examination on April 11, 2026. The program aimed to strengthen students’ proficiency in office productivity applications, a core requirement in the contemporary workplace. The Microsoft Word module focused on creating professional documents and using mail merge; the Microsoft Excel module covered functions and formulas for data processing; and the Microsoft PowerPoint module emphasized the development of interactive presentations using animations, slide design, and background images. The training was facilitated by Wilianto, S.T., S.Pd., M.M., M.TI.; M. Ayyasi Fawaz, S.Kom., M.Kom.; and Dr. Edison Parulian, S.E., M.Si. The results indicated strong participant engagement and improved understanding of Microsoft Office applications, supporting students’ preparation for the BNSP certification examination and future workplace demands.